Improvement of native pulmonary alveolar proteinosis after contralateral single living‐donor lobar lung transplantation: A case report. (27th January 2020) - Kobayashi, Kazuma; Ohkouchi, Shinya; Sasahara, Yoji; Ebina, Masahito; Nakata, Koh; Saito, Ryoko; Akiba, Miki; Sado, Tetsu; Oishi, Hisashi; Watanabe, Tatsuaki; Kurosawa, Hajime; Okada, Yoshinori
Abstract: PAP is a rare disease characterized by the accumulation of surfactant materials in the alveolar spaces due to the imbalance of surfactant homeostasis (production and clearance). We herein report a case of an 8‐year‐old girl who developed PAP after BMT from her mother for the treatment of DBA. The anemia was improved by BMT; however, respiratory dysfunction due to graft‐versus‐host disease gradually progressed. She eventually underwent right single LDLLT from her mother when she was 14 years old. A pathological examination of the excised lung confirmed the finding of diffuse bronchiolitis obliterans and unexpectedly revealed widespread alveolar proteinosis. Interestingly, the GGO of her native left lung on chest X‐ray was improved after LDLLT. We present the very unique clinical course of this patient and discuss the mechanisms underlying the development of PAP after BMT and its improvement after LDLLT from the same donor.